2022
DOI: 10.1099/acmi.0.000354
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of chlorous acid and sodium hypochlorite activity against SARS-CoV-2

Abstract: A novel coronavirus, named severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), suddenly emerged in China in 2019, spread globally and caused the present COVID-19 pandemic. Therefore, to mitigate SARS-CoV-2 infection effective measures are essential. Chlorous acid (HClO2) has been shown to be an effective antimicrobial agent. However, at present there is no experimental evidence showing that HClO2 can inactivate SARS-CoV-2. Therefore, in this study, we examined the potential of HClO2 to inactivate SAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Our data indicated that in the absence of a soil load, NaOCl at 50 ppm for 1 min resulted in 5 log reduction. The latter is a much lower concentration than reported by Chin et al and Chan et al ( 16 , 48 ), in line with 10 ppm for 3 min reported by Hatanaka et al ( 49 ), but higher than the 1.5 ppm for 30 s reported by Brown et al ( 50 ).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Our data indicated that in the absence of a soil load, NaOCl at 50 ppm for 1 min resulted in 5 log reduction. The latter is a much lower concentration than reported by Chin et al and Chan et al ( 16 , 48 ), in line with 10 ppm for 3 min reported by Hatanaka et al ( 49 ), but higher than the 1.5 ppm for 30 s reported by Brown et al ( 50 ).…”
Section: Discussionsupporting
confidence: 84%
“…These studies reported a wide range of results to achieve >3 log reduction in SARS-CoV-2. For example, in the absence of soil load, 10% bleach (unknown ppm for NaOCl) for 1 min resulted in 3.25 log reduction ( 48 ), 1:99 dilution of bleach (unknown ppm for NaOCl) for 5 min resulted in 4.8 log reduction ( 16 ), 10 ppm for 3 min resulted in 3 to 4 log ( 49 ), and 1.5 ppm for 30 s resulted in ~4 log reduction ( 50 ). Chin et al and Chan et al ( 16 , 48 ) did not consider the buffering effect of infection media in virus stocks on NaOCl.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One candidate among chlorinated compounds is chlorous acid solution [ 8 ]. Chlorous acid (HClO 2 ) has a structure with one more oxygen than hypochlorous acid.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, various chlorine-based disinfectants, such as chlorine dioxide, sodium hypochlorite, and chlorous acid solutions, have been shown to exhibit antiviral effects against SARS-CoV-2 [6][7][8][9]. This is because chlorine ions are potent oxidizing agents that induce denaturation of microbial proteins [10]; however, chlorine ions rapidly lose their antimicrobial activity upon contact with organic matter [11].…”
Section: Introductionmentioning
confidence: 99%